Harnessing the Microbiome to Enhance Cancer Immunotherapy - Nelson, Michelle H. (J Immunol Res, 2015)
The microbiota plays a key role in regulating the innate and adaptive immune system. Herein, we review the immunological aspects of the microbiota in tumor immunity in mice and man, with a focus on toll-like receptor (TLR) agonists, vaccines, checkpoint modulators, chemotherapy, and adoptive T cell transfer (ACT) therapies. We propose innovative treatments that may safely harness the microbiota to enhance T cell-based therapies in cancer patients. Finally, we highlight recent developments in tumor immunotherapy, particularly novel ways to modulate the microbiome and memory T cell responses to human malignancies.